Measurement of transport properties of aerosolized nanomaterials. (December 2015) - Ku, Bon Ki; Kulkarni, Pramod
Abstract: Airborne engineered nanomaterials such as single-walled carbon nanotubes (SWCNTs), multi-walled carbon nanotubes (MWCNTs), functionalized MWCNT, graphene, fullerene, silver and gold nanorods were characterized using a tandem system of a differential mobility analyzer and an aerosol particle mass analyzer to obtain their airborne transport properties and understand their relationship to morphological characteristics. These nanomaterials were aerosolized using different generation methods such as electrospray, pneumatic atomization, and dry aerosolization techniques, and their airborne transport properties such as mobility and aerodynamic diameters, mass scaling exponent, dynamic shape factor, and effective density were obtained. Laboratory experiments were conducted to directly measure mobility diameter and mass of the airborne nanomaterials using tandem mobility-mass measurements. Mass scaling exponents, aerodynamic diameters, dynamic shape factors and effective densities of mobility-classified particles were obtained from particle mass and the mobility diameter. Microscopy analysis using Transmission Electron Microscopy (TEM) was performed to obtain morphological descriptors such as envelop diameter, open area, aspect ratio, and projected area diameter. The morphological information from the TEM was compared with measured aerodynamic and mobility diameters of the particles. The results showed that aerodynamic diameter is smaller than mobility diameter below 500 nm by a factor of 2–4 for all nanomaterials except silver and gold nanorods. Morphologies of MWCNTs generated by liquid-based method, such as pneumatic atomization, are more compact than those of dry dispersed MWCNTs, indicating that the morphology depends on particle generation method. TEM analysis showed that projected area diameter of MWCNTs appears to be in reasonable agreement with mobility diameter in the size range from 100 to 400 nm. Principal component analysis of the obtained airborne particle properties also showed that the mobility diameter-based effective density and aerodynamic diameter are eigenvectors and can be used to represent key transport properties of interest. Highlights: Airborne nanomaterials were characterized using a tandem mobility-mass analysis. Microscopy analysis was performed to obtain morphological descriptors. Airborne transport properties such as mobility and aerodynamic diameters were measured. Aerodynamic diameter is smaller than mobility diameter below 500 nm for most nanomaterials. Principal component analysis showed that mobility diameter-based effective density and aerodynamic diameter are eigenvectors.